Studi Literatur: Model Pembelajaran Quantum Teaching Dalam Meningkatkan Keberanian Berbicara Siswa Menggunakan Media Realia - Thoriq Hasan Adikalan (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
One of the reasons for the low learning outcomes is that the learning method used by the teacher does not involve student activity and also the lack of care from the teacher to provide media in learning. The courage to speak a student is very important and needed in a class discussion, because with a student daring to speak in front of the class he has been found as an active student. The purpose of this article is to discuss the application of realia media in increasing the courage to speak students during learning or class discussion so as to increase student activity. Realia media is an object that can be seen, heard or experienced by students so as to provide experience directly to them. Quantum Teaching is an effective and fun and not boring learning model. Quantum Teaching learning steps are known as TANDUR: (1) Grow (2) Natural (3) Rename (4) Demonstration (5) Repeat and (6) Celebrate. Relevant research results show that Media Realia is able to increase student activity in asking, discussing, and expressing their opinions. Keyword: Quantum Teaching, Media Realia, Speak.